The Crutch Usage and Rehabilitation after Hip Arthroscopy Surgery: A Systematic Review - Jui-Chang Kao; Chieh-An Chuang; Hao-Che Tang; Yi-Sheng Chan (Formosan Journal of Musculoskeletal Disorders)
Background: Hip arthroscopy has emerged as a pivotal surgical intervention for various hip pathologies, including femoroacetabular impingement (FAI) and labrum tears, owing to advancements in instrumentation and technique. As the prevalence of hip arthroscopic procedures continues to rise, understanding optimal post-operative care becomes paramount for achieving favorable outcomes. Despite the recognized importance of rehabilitation in shaping post-operative results, there exists a gap in the literature regarding standardized rehabilitation protocols and the specific role of crutches in the recovery process following hip arthroscopy. Objectives: This systematic review aims to assess the variability in the utilization of crutches and rehabilitation protocols subsequent to hip arthroscopy for labrum repair, as evidenced in existing studies. Materials and Methods: A comprehensive search of PubMed, Embase, Medline, and Cochrane Library databases was conducted to identify the relevant studies pertaining to the use of crutches and rehabilitation protocols posthip arthroscopy for labrum repair. The inclusion criteria encompassed clinical studies and reviews with evidence levels ranging from I to IV, which specifically addressed crutch usage and rehabilitation protocols. Results: A total of 21 studies were ultimately incorporated into the analysis. These studies were categorized based on the hip scores employed in their evaluations. Weighted averages were calculated to ascertain the improvements in scores and duration of crutch employment. Conclusions: While the absence of a standardized guideline concerning the use of crutches and rehabilitation protocols subsequent to hip arthroscopy is evident, a generally positive stance regarding the necessity of crutch utilization persists. In addition, when crutches were integrated into the rehabilitation process, the average duration of usage extended to approximately 2 weeks. Nonetheless, optimal timing may exhibit variations upon the completion of further comprehensive studies.